2017
DOI: 10.1302/2046-3758.65.bjr-2016-0221.r1
|View full text |Cite
|
Sign up to set email alerts
|

Photofunctionalised Ti6Al4V implants enhance early phase osseointegration

Abstract: ObjectivesUltraviolet (UV) light-mediated photofunctionalisation is known to improve osseointegration of pure titanium (Ti). However, histological examination of titanium alloy (Ti6Al4V), which is frequently applied in orthopaedic and dental surgery, has not yet been performed. This study examined the osseointegration of photofunctionalised Ti6Al4V implants.MethodsTi and Ti6Al4V implants were treated with UV light, and the chemical composition and contact angle on the surfaces were evaluated to confirm photofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 20 publications
1
36
0
Order By: Relevance
“…All implants placed in tibias and femurs were unloaded. In detail, most authors reported significantly increased BIC [57,71,[73][74][75][76][77][78][79], push-in values [40,44,[80][81][82][83], bone volume [72,84], or bone mineral [85,86] were noted in all animal models studied for photofunctionalized groups disregarding implant surface modifications/topography. The differences were insignificant for both UV-treated and non-UV-treated reported in four animal studies [87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All implants placed in tibias and femurs were unloaded. In detail, most authors reported significantly increased BIC [57,71,[73][74][75][76][77][78][79], push-in values [40,44,[80][81][82][83], bone volume [72,84], or bone mineral [85,86] were noted in all animal models studied for photofunctionalized groups disregarding implant surface modifications/topography. The differences were insignificant for both UV-treated and non-UV-treated reported in four animal studies [87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%
“…The use of UV light to condition the implant surface has emerged from the knowledge of the photocatalytic degradation properties of TiO 2 based on the photo-induced hydrophilicity and decomposition reaction described above [32]. The effect of photofunctionalization on different surfaces was evaluated by many researchers, and the production of superhydrophilic surfaces with increased and accelerated bone-implant integration was demonstrated in in vitro [21,22,93] and in vivo [58,73,87,96,98] studies.…”
Section: Discussionmentioning
confidence: 99%
“…Photofunctionalised Ti implants are reported to increase the bone-implant contact ratio 2.5 times after 2 weeks, and 1.9 times after 4 weeks compared to Ti without photofunctionalization. 1 In our previous study, Yamauchi et al reported that UV-treated Ti and Ti6Al4V demonstrated signi cant differences in chemical properties and were more wettable than untreated implants [3]. Furthermore, we showed that antimicrobial activity was induced on Ti and Ti6Al4V for seven days after UV irradiation [8].…”
Section: Discussionmentioning
confidence: 54%
“…To examine the change in hydrophilicity on the disk surface after UV irradiation, the wettability was evaluated by measuring the contact angle of a water drop [3]. For this test, 10 μL of water was dropped onto the disk surface before UV irradiation, and at 0 minutes, one hour, three hours, six hours, two weeks, and four weeks after UV irradiation.…”
Section: Hydrophilicity Of the Hydroxyapatite Surfacementioning
confidence: 99%
See 1 more Smart Citation